A potência da improvisação em dança: uma abordagem arquetípica - Fiamenghi, Aline Ribeiro (2009)
This research intends to present the concept of "Soul-Making". Its basis resides in the activities of dance improvisation. According to Archetypal Psychology, "soul" is an imaginative possibility, a function of transforming events into experiences and the capacity of recognizing all realities as primarily symbolical or metaphorical. We don't intend to restrict dance experience to psychological ideas, nor explain it. We take dance as our starting-point for its power of "touching us". Dance functions as a means to create metaphors as we understand improvisation in dance like the act of imagining with the body. Dance is a search for encounters, it happens in relation to: image, music and the dancer s intellectual, artistic and corporeal repertoire as much as his connections (relations) among other dancing bodies. We believe that movement, organized as the thought of the body can produce different conscience modalities, beyond the egoic one. We show a working method, developed in two meetings, which we called Improvisation Laboratory. Our purpose was to observe the reverberations of free movements, without any previous technical preparation for the dancers. That is to say, what kind of images were produced and how they have transformed the event into an animic experience